IoT-Based Smart Kitchen for Smart Home Applications - Kulkarni, Koustubh; K. Vittapu, Sravan; Sankuru, Ravichand; Sai Priya, Bukka; Sravani, Bugga; Umesh, Dommata (Journal of Electronic Design Engineering, 2023)
One of the most important rooms in any person’s or family’s home is the kitchen. Above all else, safety is the most important consideration for any activity done in the kitchen. It is imperative to promptly detect and manage gas leaks, uncontrolled fires, high temperatures, and damp conditions to ensure everyone’s safety and to preserve groceries, essential fruits and vegetables, and other items in good condition. Making a prototype of an Internet of Things (IoT) based SMART [S-Safe, M-Monitoring, A-Analysis, & R-Reporting, T-Technology] system is the primary goal of this project. The Internet of Things (IoT) is the concept that this SMART system for the kitchen uses. Several sensors, relays, and an ESP8266-Board Node MCU are all used in this proposed system. The ESP Dashboard server keeps an eye on the parameters of the indoor environment, including temperature, humidity, and smoke and gas detectors, to ensure the desired operation. This SMART kitchen’s overarching goal is to provide a costly and practical cooking environment that optimizes convenience and minimizes hazards. Additionally, it should shield users from any unfortunate events, user errors, or carelessness on their part and encourage a safe area for cooking as well as a place to store groceries and other necessities.